The Role of Diet in Psoriasis Management: A Focus on Mediterranean, Ketogenic, and Plant-Based Dietary Approaches - Krystian Zukierski; Weronika Jarych; Katarzyna Michalak; Michał Mazur (Quality in Sport)
Introduction and aim: